PREDICTING PERFORMANCE IN SPEED CLIMBING: ACCURACY OF THE FORCE-VELOCITY TEST ON A CYCLE ERGOMETER - Krawczyk, Marcin; Pociecha, Mariusz; Sordyl, Tomasz; Stepek, Aleksnadra; Kozioł, Paulina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The present study examined the validity of the force-velocity (F-V) mechanical parameters of the lower limbs as a predictors of the competitive performance in junior male speed climbing. The second aim was to evaluate F-V characteristics in competitive speed climbers in the junior male category. Ten junior male speed climbers (age: 18±0.5 years; BH: 174.7±4.5 cm; BW: 66.4±6.6 kg; with mean best climbing time from the competition BCT: 7.29±0.66 s) were participants in the research. All they were participants in the Youth European Cup in speed climbing. F-V characteristics were measured using a cycle ergometer test according to the Vandewalle’s protocol. To evaluate of the validity between BCT (criterion) and mechanical parameters (practical measures) from F-V test a standard error of the estimate (expressed as a raw and standardized typical error, TE) and correlation coefficients (rx,y) were used. Moreover, the validity of BCT as a potentially predictor of final competition rank (as a criterion for BCT) was evaluated. Additionally the mean value and standard deviation were calculated for all measured variables. Validity of the BCT as a competition place predictor was largely overestimated (TE=0.73 and rx,y=0.81, p p≤0.05). Accuracy of the BCT prediction for somatic and mechanical variables were very largely error biased. The standardized values of TE for these variables were: 1.93÷7.25. The rx,y were in the range of -0.18 to -0.46. The level of the mechanical variables from the F-V cycle ergometer as a predictors of the BCT in speed climbing may be largely error biased. Application of the cycle ergometer F-V test of prediction BCT values in speed climbing may have low practical value. Moreover, BCT variable may be a poor predictor of the final competition result. Coaches should take these suggestions into account during preparations to speed climbing competitions.